Phenomenological Barriers to Cyber Extension Adoption among Agricultural Extension Workers - Sabaruddin Sabaruddin; Tuti Bahfiarti; Farid (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2026)
This study explored the phenomenological barriers experienced by agricultural extension workers in adopting the Cyber Extension platform in Pangkajene and Islands Regency. Using a phenomenological approach, data were collected through in-depth interviews, participatory observation, and documentation, then analyzed thematically. Four main themes emerged: (1) infrastructure limitations, especially unstable and uneven internet access in mountainous and island regions, disrupted the delivery of digital extension services; (2) low digital literacy skills, particularly among senior extension workers, was exacerbated by the lack of regular and comprehensive technology training; (3) resistance to technological change was evident in skepticism toward digital platforms, with a preference for conventional, face to face method that were perceived as more effective for farmer engagement; and (4) weak policy support and insufficient inter-agency coordination resulted in limited budget allocation, inadequate facilities, and fragmented training programs. These structural gaps forced extension workers to rely on personal resources to sustain implementation. The findings indicated that digital transformation in agricultural extension requires not only reliable infrastructure but also targeted capacity building, cultural readiness, and strong institutional backing. A holistic, context-sensitive strategy is essential to optimize Cyber Extension adoption, particularly in areas facing geographical challenges.